Chemical-induced occupational asthma: A case series - Rakesh Kumar Singh; Parul Mrigpuri; Balakrishnan Menon; Mridul Sarma (Indian Journal of Allergy Asthma and Immunology)
Exposure to a variety of chemicals is known to have adverse consequences, occupational asthma being one of them. Isocyanate exposure has been found to be associated with airways obstructive abnormalities, but Indian data in this context are scarce. Similarly, the reports on the association of potassium permanganate (KMnO4) with asthma are very limited. We hereby present two cases of occupational asthma related to exposure of acrylic polyurethane, KMnO4, and sodium hypochlorite.